2021
DOI: 10.1002/ajmg.a.62083
|View full text |Cite
|
Sign up to set email alerts
|

Novel FOXP1 pathogenic variants in two Indian subjects with syndromic intellectual disability

Abstract: We describe two unrelated Indian boys with Mental retardation with language impairment with or without autistic features (OMIM#613670). Novel pathogenic variants c. 593_599 delins AGAAG and c.1556T>C in FOXP1 were identified in Patients 1 and 2, respectively by exome sequencing. The patients shared the cardinal features of significant language impairment, prominent forehead, downslanted palpebral fissures, frontal upsweep of hair, and behavioral abnormalities. Camptodactyly (with pterygia in Patient 2) was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Subject P2 has been described previously (Moirangthem & Phadke, 2021). He had developmental delay, mainly language impairment, macrocephaly, and dysmorphic features (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…Subject P2 has been described previously (Moirangthem & Phadke, 2021). He had developmental delay, mainly language impairment, macrocephaly, and dysmorphic features (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the 11 cases reported in the systematic review, two cases were reported later and showed strabismus [4,5].…”
Section: Discussionmentioning
confidence: 96%
“…This patient also had strabismus that was corrected surgically. In addition to the 11 cases reported in the systematic review, two cases were reported later and showed strabismus [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%